Effect of daily mindfulness fluctuations on sleep and recovery-stress states in elite level judoka: an observational study - Birnkraut, Tim; Kellmann, Michael; Jakowski, Sarah (Frontiers in Sports and Active Living, 2025)
IntroductionSleep is a fundamental factor in an athlete's ability to sustain peak performance and endurance. Mindfulness, defined as a state of intentional, non-judgmental awareness of the present moment, has been linked to positive effects on sleep. The present study aims to investigate which recovery and sleep parameters are influenced by interindividual differences in mindfulness tendencies and intraindividual daily fluctuations in mindfulness.MethodsA two-week continuous monitoring study was conducted with 33 elite-level judoka (17 female, 16 male; age: M = 23.79, SD = 3.05) competing at the national and international level. Data collection included objective sleep monitoring via actigraphy and subjective monitoring through morning and evening self-report questionnaires. Sleep was analyzed as a function of both trait and daily mindfulness, as well as behavioral factors such as the number of training sessions, session intensity, and the implementation of recovery activities and naps.ResultsMultilevel analyses revealed significant positive associations between mindfulness and qualitative subjective sleep parameters, as well as morning and evening recovery-stress states. Among the mindfulness facets, acting with awareness emerged as the strongest predictor. In terms of quantitative sleep parameters, mindfulness influenced both subjective and objective sleep latencies.DiscussionThe findings suggest that mindfulness may play a key role in sleep regulation among athletes, particularly in enhancing perceived restfulness, improving recovery-stress states in the evening and morning, and facilitating the process of falling asleep. These results highlight mindfulness as a promising target for interventions aimed at improving subjective recovery and reducing sleep onset latencies through daily mindful behaviors. Furthermore, the study underscores the relative independence of qualitative and quantitative sleep parameters, suggesting they are influenced by distinct factors.